Strategi Pengembangan Usaha Dan Perubahan D’sruput Dalam Ketertarikan Minuman Kekinian Terhadap Minatbeli Konsumen Kalangan Muda - Fary Pratama Putra; Rafli Alfaredo; Sandya Paramunitia; Vallery Rahmi Vilyan; Ramdani Bayu Putra (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Contemporary drinks are rife among young people. The competition between the beverage outlets can be seen from the emergence of various unique beverage outlets. For this reason, the authors are interested in examining the factors of modern drinking interest in buying interest among young consumers. This research uses a qualitative descriptive method, and the respondents are taken from young people in Padang who like modern drinks. Based on the results of interviews and observations obtained in the field, it was found that there were several factors of interest so that there was an interest in buying among young people, namely factors of a comfortable place, friendly service, factors of good taste where there were many variants, factors of restaurant names and unique menu names that made people interested in buying. Besides that, the price factor is quite affordable, packaging with a creative and attractive design. In addition, it was also found that personal, social and psychological factors were one of the factors in the interest in buying contemporary drinks among young people. It is hoped that this research will be useful for business people in the culinary and beverage sector as well as further research in researching business in this field.